A influência da regulação emocional dos pais no desenvolvimento infantil dos filhos: diferenças por gênero parental - Maffazioli, Ana Carolina (2020)
Maffazioli, A. C. (2020). The influence of emotional regulation of parents on the children's child development: differences by parental gender. Master’s dissertation, Graduate Program in Psychology, Universidade Federal do Espírito Santo, Vitória/ES. 88 p. Child development is greatly influenced by the regulators present in the child's life, who usually to be the parents during the early childhood. Therefore, an adequate parenting is very important to ensure the child development. Although it has not yet been studied, the emotional regulation has impact on this development. Considering that the self-regulation is important for the human adaptation and development in different contexts of interaction and the parents are important co-regulators of their children, a parenting practice not supported by the parents' emotional regulation can result in risks for the child development. Therefore, the objective of this Dissertation was to investigate the relationship between parental emotional regulation and child development, in general and by domains, of kids between 24 and 35 months of age, comparing the parental genders. Based on this, two studies were conducted. The Study 1 was a comparative research design between fathers and mothers to evaluate differences between genders on the parental emotional regulation. Data from a sample of 47 mothers and 33 fathers were analyzed descriptively, comparing means and standard deviations of parental emotional regulation evaluated by the PERS, Parents Emotion Regulation Scale, composed by four domains: 1- Orientation to children's emotions; 2- Avoidance of the child's emotions; 3- Lack of emotional control; and 4- Acceptance of emotions, both own and those of the child. The Mann-Whitney and Spearman's correlation tests were used to compare measures of central tendency between fathers and mothers, as well as to verify associations between them and related variables. The results showed that the maternal means tend to be higher than the paternal ones, with significant differences in the “Orientation of the child's emotions” (p = 0.000) and “Acceptance of emotions, both their own and those of the child” (p = 0.037) domains. Regarding the related variables, the parent was correlated with the age correlated with the “Orientation of the child's emotions (rho = 0.413)” and “Acceptance of emotions, both their own and those of the child” (rho = 0.345) domains, that highlight that how much higher the father age, more high his emotional regulation scores on those EREP domains. About mothers, the maternal job (weekly hours worked) was correlated with the “Acceptance of emotions, both her own and those of the child” (rho = 0.321) scores, showing that the mothers who work more hours a week have greater emotional acceptance. This study concluded that there are gender differences in the parenting that can be justified by the Brazilian culture, where the macho culture has impacts on the man, who learns to avoid his emotions, and the woman, who expresses her emotional responses more easily. Based on the general objective of this Dissertation, the objective of Study 2 was to analyze relations between parental emotional regulation and development of kids, conducted on a transversal exploratory design with 47 families with kids between 24 e 35 months old, who were evaluated by the Battelle Developmental Inventory Screening, Brazilian version. Descriptive statistical analyzes were conducted and Spearman correlations were tested to verify relations among the parental emotional regulation and the child development domains. The results showed that, for mothers, the domain "Orientation to the child's emotions" was significantly correlated with the adaptive domain (rho = 0.316); while “Lack of emotional control” was correlated with the general development (rho = -0.304), as well as with and the personal-social (rho = -0.340) and motor domains (rho = -0.328). For parents, the “Lack of emotional control” domain was correlated with the cognitive (rho = 0.368) and communicative (rho = 0.361) domains of child development. These results showed that the relationships between the parental emotional regulation and the child development differ among mothers and fathers, with a greater tendency for the maternal emotional regulation to be related to the child development. Studies with new hypotheses are important to analyze the impacts of parental emotional regulation on the child development, exploring others related variables from parents and their kids.